Measuring the Non Observed Economy : A Handbook. (International Monetary Fund, 2002)
Good-quality, comprehensive national accounts are vital for economicpolicymaking and research. Exhaustive coverage is difficult to achieve,however, because some economic activities may be illegal, informal,household production for own final use, or missed because of deficienciesin the data collection system. Such activities are said to constitute thenon-observed ("hidden," "underground," or "shadow") economy. ThisHandbook - the product of collaboration among the OECD, the IMF, ILO, ISC-CIS - identifies best practices for measuring the non-observed economy, consistent with international standards (in particular, with theSystem of National Accounts 1993).